Staying Together: NatureCulture in a Changing World - Mondal, Kaushani (Lexington Books, 2023)
Staying Together: Natureculture in a Changing World is about staying together, living together, and the dynamics and poetics of togetherness. It demonstrates, through a strong investment in nature studies, nonhuman studies, and nature culture and cohabitative readings, a commitment to interconnectedness. The contributors speak of co-habitation, a kind of co-presence that happens for the good of all and has been happening before we realized its prevalence. They argue co-beingness is deeply founded in difference, differentiation, and dispersion. They explore and investigate this fraught and profound “weness” at a variety of levels, and look at forms of biocentrism and bioegalitarianism where there are opportunities for the affirmation of difference as much as declaration of complexities in co-specicism, co-occurrence, and co-being. The book answers the following questions: How can the complexity of sustainability and survivality lead us to re-planetize the planet? Are we unworlding an Earth where the meaning and ethos “being together” demand reinvention and rearticulation?